An attempt towards coordination supramolecularity from Mn(II), Ni(II) and Cd(II) with a new hexadentate [N4O2] symmetrical Schiff base ligand: Syntheses, crystal structures, electrical conductivity and optical properties - Sarkar, Saikat; Biswas, Susobhan; Liao, Meng-Sheng; Kar, Tapas; Aydogdu, Yildirim; Dagdelen, Fethi; Dey, Kamalendu (Pergamon-Elsevier Science Ltd, 2008)
To explore the influence of non-covalent weak force interactions, mainly exerted by carboxylic groups, on the formation of supramolecular architectures of transition metal complexes and their electrical conduction processes, a new symmetrical [N4O2] hexadentate Schiff base ligand, 1,8-N-bis(3-carboxy)disalicylidene-3,6-diazaoctane-1,8-diamine, abbreviated to H(4)fsatrien, and its complexes of Ni(II), Cd(II) and Mn(II) have been synthesized using in situ condensation of the ligand components in the presence of metal ions. The complexes were structurally characterized by elemental analyses, IR, UV-Vis, NMR. ESR, molar conductivity and magnetic measurements. The crystal structures of all the complexes have been determined by a single crystal X-ray diffraction study. The 1-D, 2-D and 3-D networks of the complexes are formed by pi-pi stacking, C-H...pi interactions and mono or bifurcated H-bonding. The electronic structures of the complexes have been examined using the DFT method. Solid-state properties (e.g. electrical conductivity at different temperatures and optical properties) of the Ni(II) and Mn(II) complexes have also been studied and, depending on the temperature, the conductivity of the complexes is found to be insulating and semiconducting (intrinsic and extrinsic) in nature. The optical band gap (E-gd) of complexes (1) and (3) is found to be 2.57 and 2.30 eV, respectively. (C) 2008 Elsevier Ltd. All rights reserved.
Keywords: Schiff base; Self-assembly; Crystal structure; Activation energy; DFT